1990
DOI: 10.1530/acta.0.1230405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of danazol and goserelin on insulin and glucagon in non-obese women with endometriosis

Abstract: To investigate the effects of medical treatment of endometriosis on concentrations of insulin and glucagon in comparison with those of androgens, 12 nonobese women with minimal endometriosis were randomly allocated to receive treatment with either danazol or the gonadotropin-releasing hormone analogue, goserelin. In subjects treated with danazol, mean (sd) summed serum insulin (1.08 (0.22) nmol/l pretreatment; 3.00 (1.50) nmol/l after treatment, p<0.05) and summed plasma glucagon (94 (21) pmol/l pretreatment; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…The results suggest that as concentrations of total testosterone and androstenedione increase, those of glucagon decrease, a pattern of response opposite to that proposed or which has been identified in other hyperglucagonaemic states. These data do not establish whether testosterone and androstenedione directly influence concentrations of glucagon in plasma, although we have been unable to show any correlation between changes in the concentrations of total or free testosterone or androstenedione and those of glucagon associated with the administration of either danazol or goserelin (Golland et al, 1990).…”
Section: Discussioncontrasting
confidence: 72%
“…The results suggest that as concentrations of total testosterone and androstenedione increase, those of glucagon decrease, a pattern of response opposite to that proposed or which has been identified in other hyperglucagonaemic states. These data do not establish whether testosterone and androstenedione directly influence concentrations of glucagon in plasma, although we have been unable to show any correlation between changes in the concentrations of total or free testosterone or androstenedione and those of glucagon associated with the administration of either danazol or goserelin (Golland et al, 1990).…”
Section: Discussioncontrasting
confidence: 72%
“…Women with ovarian hyperandrogenism frequently have hyperinsulism with insulin resistance [38,39]. Administration of androgens or ana bolic steroids has been found to decrease insulin sensitiv ity and impair glucose tolerance [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…We have found that long-term therapy leads to a significant decrease in serum SHBG levels over time. This may be the result of a drug-induced decrease in ovar ian estrogen production, given that it is known that estro gen stimulate SHBG synthesis in the liver [21], However, the goserelin-induced decrease in SHBG seems to be a delayed effect, because no change has been observed in the serum SHBG levels of nonobese women with endome triosis after 6 weeks of therapy [22],…”
Section: Time On Treatment Weeksmentioning
confidence: 99%